An Evaluation of Pros and Cons Indulged in Application of Green Supply Chain in Manufacturing Companies - Devi B Devaru, Susheela (International Journal of Psychosocial Rehabilitation, 2024)
In recent years, the concept of green supply chain management has started gaining importance in India in spite of unclear regulations from the government. Logistics involve not only transportation but also warehousing, packaging, inventory management, and material handling. All these activities in logistics make a substantial adverse impact on the environment. Green logistic practices are the need of the hour to reduce the impact on the environment and gain a competitive advantage. The major objective of this paper is to empirically analyze the major barriers to implementation of green logistics and to statistically rank the best green logistics practices with respect to the manufacturing sector. A quantitative approach was carried out to find out the barriers to green logistics and filter out the best green practices with the help of the survey conducted among the middle-level managers in the operations department of different organizations in the manufacturing sector. This study will help the decision-makers  understand the significance of GSCM.